A TINJAUAN ANALISIS KESALAHAN MAHASISWA PADA MATA KULIAH ALJABAR LINEAR BERDASARKAN MODEL TAHAPAN KASTOLAN - Robert Harry Soesanto (De Fermat : Jurnal Pendidikan Matematika, 2021)
Studies that highlight the scope of mathematics learning still become continuous discussion topics. Numerous findings have the potential to be a discussion for further research. In mathematics learning, there are many problems in the form of mathematical errors made by learners in solving problems. This descriptive qualitative research aims to review mathematical errors made by students in Linear Algebra courses. Error analysis model using Kastolan stages that focus on 3 types of errors namely conceptual, procedural, and technical errors. A total of 30 students of Mathematics Education study program from Pelita Harapan University were given question to analyze their mistakes. Data analysis was performed using Miles and Huberman technique which included data collection, data presentation, and conclusion. The results showed that as many as 50% of students underwent conceptual errors, 20% of students underwent procedural errors, 3.33% of students underwent technical errors, and 26.67% of students underwent no errors. These findings provide an opportunity for researchers to analyze other mathematical learning with Kastolan stages as well as encourage researchers to develop learning models to minimize mathematical errors made by students.